(untitled) (Transport systems and technologies, 2021)
Maintaining a high level of maintenance of electrical equipment in passenger cars requires research in the field of improving methods and means of technical diagnostics. Electronic devices for automatic control and protection, which are located in the switchboard of the car, are one of the most critical elements in the electrical equipment system, ensuring its reliable, efficient and safe operation. If the automatic adjustment and protection devices are out of regulation during operation, the voltage and current in the electrical equipment network may exceed the permissible level, which leads to the failure of electricity consumers, a battery and a generator. In addition, the semiconductor devices themselves are very sensitive to short-term overloads, in which, even with minor overloads, a breakdown or breakage of the conductive layer occurs. Modern trends in the development of passenger car fleet indicate a sharp increase in the complexity of the element base of cars. This mainly concerns the electrical systems of cars, where all the functions of control, monitoring and diagnostics are performed by electronics. Maintaining a high level of service for such systems requires research in the field of improving methods and means of technical diagnostics. For these purposes, the authors have developed a method for constructing optimal control and diagnostic tests, which is based on a combinatorial approach. The method is easily implemented on a computer.